2012
DOI: 10.1111/j.1742-4658.2012.08674.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional regulation of Slug / Snail2 is dependent on GSK‐3β‐mediated phosphorylation

Abstract: Snail family proteins regulate transcription of molecules for cell-cell adhesion during epithelial-mesenchymal transition (EMT). Based on putative glycogen synthase kinase 3β (GSK-3β) phosphorylation sites within the Slug/Snail2, we explored the significance of GSK-3β-mediated phosphorylation in Slug/Snail2 expression during EMT. Mutation of the putative GSK-3β phosphorylation sites (S92/96A or S100/104A) enhanced the Slug/Snail2-mediated EMT properties of E-cadherin repression and vimentin induction, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 27 publications
1
58
0
1
Order By: Relevance
“…Moreover, SLUG staining, rather than being nuclear, appeared predominantly cytoplasmic in the OFT endothelium of Nrp1-null mutants ( Figure 10D). A similar staining pattern was previously observed in cells with impaired SLUG phosphorylation (47), raising the possibility that cytoplasmic SLUG staining in Nrp1-null OFTs reflects dysregulated signaling. mutants had normal cardiac NCC migration into the OFT disagrees with prior studies in chick, in which siRNA-mediated NRP1 targeting impaired this process (14).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, SLUG staining, rather than being nuclear, appeared predominantly cytoplasmic in the OFT endothelium of Nrp1-null mutants ( Figure 10D). A similar staining pattern was previously observed in cells with impaired SLUG phosphorylation (47), raising the possibility that cytoplasmic SLUG staining in Nrp1-null OFTs reflects dysregulated signaling. mutants had normal cardiac NCC migration into the OFT disagrees with prior studies in chick, in which siRNA-mediated NRP1 targeting impaired this process (14).…”
Section: Discussionmentioning
confidence: 52%
“…Although it has been shown that E-cadherin is repressed by Slug (Kim et al 2012;Peinado et al 2007;Vergara et al 2010;Yoshida et al 2009), some studies show that EOC cells do not always undergo a full and classical EMT (Davidson et al 2012;Peinado et al 2007). For instance, E-cadherin was found to be up-regulated in some ovarian neoplasm cells (Davidson et al 2012;Rodriguez et al 2012;Sundfeldt et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Snail2 also contains 2 GSK-3b motifs inside the Slug domain in a recently identified Serine rich region that alike Snail1 affects ubiquitination and degradation by b-TrCP1, although this sequence does not contain the classical b-TrCP1 destruction motif. 84,85 Besides phosphorylation of the substrate, an active SCFb-TrCP1 complex requires the neddylation (incorporation of the small protein Nedd8) of Cul1 by a Nedd8-E3 ligase. 86 Interestingly, TNF-a promotes the induction of the COP9 signalosome 2 protein (CSN2) that removes Nedd8 (or reverses neddylation) from cullins increasing Snail1 stabilization during inflammation.…”
Section: Scf-b-trcp1/fbxw1mentioning
confidence: 99%